Congenital adrenal hyperplasia: hospital based study - Alzubaidi, Munib A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Congenital adrenal hyperplasia is a family of autosomal recessive disorders of cortisol biosynthesis. Depending on the enzymatic step that is deficient, there may be signs, symptoms, and laboratory findings of mineralocorticoid deficiency or excess; incomplete virilization or premature puberty in affected males; and virilization or sexual infantilism in affected females. The most frequent is 21-hydroxylase enzyme deficiency, accounting for more than 90% of cases. Objectives: to review cases of congenital adrenal hyperplasia registered in children welfare teaching hospital- medical city- Baghdad. Patients and method: This study included all patients who were presented and registered in the endocrine clinic of the children welfare teaching hospital- medical city complex as a case of congenital adrenal hyperplasia from the 1st of January 1990 till the 1st of Jun 2009. Demographic informations together with epidemiological, clinical, diagnostic and therapeutic data of the patients were collected. Results: The total number of patients was 60 patients with mean age (6.321) +/- (3.996) SD and male to female ratio of 2:3. Seventy percent of patients presented within the 1st 6 months of life, 61.9% of them were females. Thirty-one (51.7%) patients were delivered in the hospital including 72% of those who were presented within the 1st month. Forty six (76.7%) patients were presented with ambiguous genitalia with or without other presentations, 8 (13.3%) patients presented with salt losing only and 6(10%) patients presented with pseudo precocious puberty with or without other presentations. Consanguinity between the parents was present in 86.7% of patients, 33.3% of patients had positive family history of similar condition, 36.7% of patients had positive family history of neonatal death due to dehydration or abortion and only 3.3% of patients had history of hormonal therapy during pregnancy. Twenty two (36.7%) patients were reared with false sex, 95.5% of them were females reared as males, 33.3% of them accept to change their names & sex of rearing to definitive sex as females and one male (4.5%) patient reared as female had change his name and sex to male. Seventy percent of patients were diagnosed as 21 hydroxylase deficiency, both salt loser (71.4%) and non salt loser (28.6%), (10%) as 11 hydroxylase deficiency, (18.3%) as 3β hydroxysteroid dehydrogenase deficiency both salt loser (54.5%) and non salt loser (45.5%) and (1.7%) as17 hydroxylase deficiency. Conclusions: The commonest form of congenital adrenal hyperplasia in Iraq is 21 hydroxylase deficiencies. There was delay in the diagnosis in spite of hospital delivery, and this may lead to psycho-social problems for the patients and their families regarding changing the sex of rearing. Many patients having genital anomalies did not operate upon yet.